Impacts of Canada's cannabis legalization on police‐reported crime among youth: early evidence. (4th June 2021) - Callaghan, Russell C.; Vander Heiden, Julia; Sanches, Marcos; Asbridge, Mark; Hathaway, Andrew; Kish, Stephen J.
Abstract: Aims: Canada's 2018 Cannabis Act allows youth (age 12–17 years) to possess up to 5 g of dried cannabis (or equivalent) for personal consumption/sharing. This study assessed whether the Cannabis Act was associated with changes in police‐reported cannabis offences among youth in Canada. Design: Time series model using national daily criminal incident data from January 1, 2015–December 31, 2018 from the Canadian Uniform Crime Reporting Survey (UCR‐2). Seasonal autoregressive integrated moving average time series models, stratified by sex, assessed the relations between legalization and youth cannabis‐related offences. Setting: Canada, 2015–2018. Cases: Police‐reported cannabis‐related offenses among youth age 12–17 years (male, n = 32 178; female, n = 9001). Measurements: Outcomes: police‐reported cannabis‐related crimes, property crimes, and violent crimes. Covariate: calendar‐month. Findings: For females, legalization was associated with a step‐effect decrease of 4.56 (95% confidence interval [CI] = 3.32, 5.81; P < 0.001) police‐reported cannabis‐related criminal offences per day, an effect equivalent to a 64.6% (standard error [SE] = 33.5%) reduction. For males, legalization was associated with a drop of 12.73 (95% CI = 8.82, 16.64; P < 0.001) cannabis‐related offences per day, equaling a decrease of 57.7% (SE = 22.6%). Results were inconclusive as to whether there were associations between cannabis legalization and patterns of property crimes or violent crimes. Conclusions: Implementation of the Cannabis Act in Canada in 2018 appears to have been associated with decreases of 55%–65% in cannabis‐related crimes among male and female youth.